Evaluation of Aerology Diagrams and Analysis of Upper-Air Information Using RAOB and ECMWF Model Data During Significant Weather Events at Minangkabau Meteorological Station - Zikri, Muhammad Aulia; Simangunsong, Sabam Mikhael; Alamin, Mirza Virgianysah; Youwe, Angelina Serena Gracella Nesty; Kristianto, Aries (Jurnal Teras Fisika: Teori, Modeling, dan Aplikasi Fisika, 2025)
This research investigates the analysis of atmospheric conditions using radiosonde data and the ECMWF ERA5 model for extreme weather events at Minangkabau International Airport, West Sumatra. The study measures atmospheric stability indices and other parameters obtained from observational data and the model. Using a Skew-T Log-P diagram, the analysis shows that atmospheric conditions on January 16, 2024, and January 27, 2024, were volatile, supporting the development of extreme weather phenomena such as thunderstorms. CAPE value on January 16 was 2898 J/kg (observations) and 3345 J/kg (model). The correlation between observational data and the ECMWF model shows very high results, with correlation values of 0.9970 on March 8, 2024, and 0.9977 on April 2, 2024, indicating that the ECMWF model accurately represents atmospheric conditions. This research proves that the ECMWF model is reliable for weather forecasting at Minangkabau International Airport.